Interaction effects of teaching methods and gender on students' achievement and interest in Microsoft Word - Uchenna Favour Muogbo; Chinwe Juliana Enemuo (Lembaga Riset Mutiara Akbar, 2026)
This study examined the interaction effects of teaching methods and gender on students’ academic achievement and interest in learning Microsoft Word among senior secondary school students in Anambra State, Nigeria. A quasi-experimental pretest–posttest non-equivalent group design was adopted using 196 SS2 students selected from four secondary schools in the Nnewi Education Zone. Data were collected using the Computer Studies Achievement Test (CSAT) and Computer Studies Interest Scale (CSIS), with reliability coefficients of 0.90 and 0.89 respectively. Mean, standard deviation, and Analysis of Covariance (ANCOVA) were used for data analysis. The findings revealed that experiential learning significantly improved students’ achievement and interest compared to the conventional lecture method. Female students exposed to experiential learning achieved higher academic performance gains, while male students demonstrated greater increases in learning interest. The study also established significant interaction effects between teaching methods and gender on both achievement and interest in Microsoft Word. These results indicate that experiential learning promotes active participation, enhances digital literacy skills, and creates more engaging classroom experiences. The study concludes that experiential learning is a more effective instructional strategy for computer studies and recommends its integration into secondary school curricula to support inclusive and technology-oriented learning environments.